Regulatory integration across borders : public-private cooperation in transnational regulation / Rebecca Schmidt. - Schmidt, Rebecca, 1983- (Cambridge studies in transnational law, 2018)
This book deals with a key feature of globalization: the rise of regulation beyond the state. It examines the emergence of transnational regulatory cooperation between public and private actors and pursues an inquiry that is at once legal, empirical and theoretical. It asks why a private actor and an international organization would regulate cooperatively and what this tells us about the material meaning of concepts such as 'expertise', 'authority' and 'legitimacy' in specific domains of global governance. Additionally, the book addresses the structures and patterns in which cooperation evolves and how this affects the broader global order. It does so through an investigation of two public-private cooperative agreements: one between the International Standards Organization, the Organisation for Economic Co-operation and Development, the Global Compact and the International Labor Organization and one between the International Olympic Committee and the United Nations Environment Programme.